(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study investigates the distribution of allelic and genotypic forms of the rs522616 polymorphism in the MMP3 gene among patients diagnosed with cerebral arteriovenous malformations (AVMs) and a control group of healthy individuals. AVMs are congenital vascular anomalies of the brain, characterized by abnormal arterial-venous connections that bypass the capillary system. Although the condition is relatively rare, it carries significant risk due to complications such as intracranial hemorrhage and seizures. The rs522616 polymorphism (A/G) in the MMP3 gene may influence the expression of matrix metalloproteinase-3, an enzyme involved in vascular remodeling and extracellular matrix degradation. This study analyzed 154 individuals, including 94 AVM patients and 60 healthy controls, to assess the prevalence and potential pathological relevance of the polymorphism. The genotypic and allelic distributions were evaluated using standard case-control statistical methods, including Hardy-Weinberg equilibrium testing and chi-square analysis. The results revealed that the A allele was predominant in both groups, while the G allele—considered potentially unfavorable—was slightly more common among AVM patients, particularly those with hemorrhagic complications. Although the differences were not statistically significant, trends suggested that individuals with the homozygous G/G genotype may have a higher predisposition to severe clinical manifestations such as hemorrhage. Subgroup analyses (hemorrhage, seizure, and other neurological deficits) further supported these observations. This study contributes to the limited but growing body of literature on the genetic basis of AVMs and highlights the potential role of the rs522616 polymorphism in MMP3 as a genetic marker of susceptibility and disease severity. While preliminary, the findings underscore the need for further large-scale investigations in diverse populations to validate the role of this polymorphism and its interaction with clinical phenotypes.